2023
DOI: 10.1002/cam4.6101
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy or antiangiogenic therapy plus chemotherapy as first‐line treatment of patients with PD‐L1(‐) advanced non‐squamous non‐small cell lung cancer in a Chinese cohort

Abstract: Purpose: For patients with advanced nonsquamous non-small cell lung cancer (NSCLC), immunotherapy or antiangiogenic therapy combined with pemetrexed and cisplatin/carboplatin have both shown significant efficacy at programmed cell death ligand 1 (PD-L1) levels of <1%. Our study aimed to compare two firstline regimens for patients with advanced nonsquamous NSCLC who were negative for PD-L1.Methods: A retrospective cohort study was conducted comparing the outcomes of patients with advanced PD-L1(-) nonsquamous N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The biomarker subgroup analysis from the IMpower150 trial indicated that IBC treatment yield superior PFS but not OS compared with BC, while IC treatment generated similar OS compared with BC (Socinski et al 2021 ). In addition, two small-sample retrospective studies compared the first-line efficacy of IC and BC in lung adenocarcinoma patients, but controversial conclusions were obtained (Xia et al 2023 ; Huang et al 2022 ). Huang et.al observed similar PFS and OS in IC and BC groups, while Xia et.al found BC has longer PFS and OS in PD-L1-negative NSCLC compared with IC.…”
Section: Discussionmentioning
confidence: 99%
“…The biomarker subgroup analysis from the IMpower150 trial indicated that IBC treatment yield superior PFS but not OS compared with BC, while IC treatment generated similar OS compared with BC (Socinski et al 2021 ). In addition, two small-sample retrospective studies compared the first-line efficacy of IC and BC in lung adenocarcinoma patients, but controversial conclusions were obtained (Xia et al 2023 ; Huang et al 2022 ). Huang et.al observed similar PFS and OS in IC and BC groups, while Xia et.al found BC has longer PFS and OS in PD-L1-negative NSCLC compared with IC.…”
Section: Discussionmentioning
confidence: 99%